Optimization of pulsed electric fields-assisted thawing process conditions and its effect on the quality of Zhijiang duck meat - Yanyang Wu; Yan Xu; Qingwu Shen; Tingxia Xu; Zhuoqi Dong; Aihua Lou (Food Chemistry: X)
Freezing storage is a common preservation method for industrialized duck meat. However, both the frozen storage and thawing processes of meat can affect meat quality. Therefore, appropriate thawing methods are crucial for maintaining good meat quality. In this study, a pulsed electric field (PEF) was used for thawing zhijiang duck meat and the freshed duck meats were used as control. Optimization of the PEF-assisted thawing process and its effect on the quality of zhijiang duck meat were analyzed. Our data showed that the shear force in the 2 kV/cm PEF-assisted thawing group was the lowest in PEF-assisted thawing groups. The color of zhijiang duck meat in the 2 kV/cm PEF-assisted thawing group was optimal. The 2 kV/cm PEF-assisted thawing could improve the texture characteristics of zhijiang duck meat and enhance water holding capacity of zhijiang duck meat. PEF-assisted thawing could better maintain the microstructure of zhijiang duck meat. Our data showed that if the intensity or duration of PEF treatment is too high, the quality of duck meat will actually decrease. Therefore, appropriate parameters should be selected in practical applications, which will provide a reference for the application of PEF-assisted thawing on the market.